Comparative Study of Hamka and Quraish Shihab's Interpretation: Application of Gadamer's Hermeneutics in Qs. Al-Maidah [5]: 51 - Luthfi, I'syatul; Raisa Zuhra Salsabila Awaluddin; Safri Nurjannah; Moh. Isbat Alfan Ghoffari (Journal of Islamic Civilization, 2022)
Hamka and Quraish Shihab have a different understanding of the interpretation of QS. al-Maidah [51]. Hamka interprets this verse as an absolute prohibition of making non-Muslims as leaders. While Quraish Shihab interprets this verse not as an absolute prohibition, so that Quraish Shihab argues may make non-Muslims as leaders with certain conditions. This article will analyze the factors causing the differences in their interpretations with Gadamer's hermeneutic approach. Gadamer's hermeneutics is chosen because for Gadamer the result of understanding or interpretation is strongly influenced by the author's pre-understanding and context. In analyzing an interpretation, Gadamer considers four things, namely Consciousness Influenced by History, Pre-understanding, Hermeneutic Circle and assimilation and Application. After analyzing the interpretations of Hamka and Quraish Shihab using Gadamer's Hermeneutics theory, it can be concluded that the differences in their interpretations are influenced by the context of their lives and different educational backgrounds. Hamka lived when political relations in Indonesia between Muslims and non-Muslims were tense. Meanwhile, Quraish Shihab lived when politics in Indonesia was no longer heated and the lives of Muslims and non-Muslims in Indonesia were harmonious. Analysis of interpretation by considering the author's horizon encourages the creation of objectivity in assessing a work of interpretation. Hamka dan Quraish Shihab memiliki pemahaman yang berbeda mengenai penafsiran QS. al-Maidah [51]. Hamka menafsirkan ayat ini sebagai larangan mutlak menjadikan non-Muslim sebagai pemimpin. Sedangkan Quraish Shihab menafsirkan ayat ini bukan sebagai larangan mutlak, sehingga Quraish Shihab berpendapat boleh menjadikan non-Muslim sebagai pemimpin dengan syarat tertentu. Artikel ini akan menganalisis faktor-faktor penyebab perbedaan penafsiran mereka dengan pendekatan hermeneutika Gadamer. Hermeneutika Gadamer dipilih karena bagi Gadamer hasil pemahaman atau  interpretasi sangat di pengaruhi oleh pra-pemahaman dan konteks pengarang. Dalam menganalisis sebuah interpretasi, Gadamer mempetimbangkan empat hal, yaitu Consciousness Influenced by History, Pre-understanding, Hermeneutic Circle and assimilation and Application. Setelah menganalisis penafsiran Hamka dan Quraish Shihab menggunakan teori Hermeneutika Gadamer dapati disimpulkan bahwa perbedaan penafsiran mereka dipengaruhi oleh  konteks kehidupn dan backroug pendidikan yang berbeda. Hamka hidup saat hubungan politik di Indonesia antar Muslim dan non-Muslim tengah tegang. Sedangkan Quraish Shihab hidup di saat politik di Indonesia tidak lagi memanas dan kehidupan muslin dan non-muslim di Indonesia sudah harmonis. Analisis penafsiran dengan mempertimbangkan horizon pengarang mendorong terciptanya objektif dalam menilai sebuah karya tafsir.